The Effect of Discovery Learning Based on Blended Learning on Student Learning Outcomes at SMA Negeri 1 Boliyohuto - Fatmawati Linggile; Supartin Supartin; Citron S. Payu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study aims to determine the effect of the blended learning-based discovery learning model on student learning outcomes on sound waves. This research was conducted in the odd semester of the 2021/2022 academic year. The research method is an experiment using one experimental class and two replication classes. This research was carried out in SMA Negeri 1 Boliyohuto in class XI IPA 1 with a total of 25 students, class XI IPA 2 with a total of 26 students, and class XI IPA 4 with a total of 27 students. The data collection of learning outcomes is based on the test results. Research data analysis using normality test, hypothesis testing, and n-gain test. Based on hypothesis testing, the experimental class obtained tcount 5.97 and ttable 2.78, replication class 1 obtained tcount 7.76 and ttable 2.77, and replication class 2 obtained tcount 6.25 and ttable 2.77. The hypothesis from the three classes H0 received because tcount>ttable. It influences the blended learning-based discovery learning model on student learning outcomes on sound wave material with high n-gain.